Infancia, adolescencia y trauma psicosocial en Medellín (1996)
ABSTRACT: The traumatic psychosocial and physical consequences in children and adolescents are derived from demographic, physical, environmental, social, cultural and economic factors that may produce risks. They can be physically manifested in lacerations, injuries or traumas and psychologically manifested in psychic trauma. If to the physical consequences we add other conditions such as marginality, involuntary displacement (internal or external) and the lack of education or job opportunities, the numbers notoriously increase on child and adolescent abuse and psychological trauma. Psychological trauma, even without organic lesion, it is considered, according to Martín-Baró "the crystallization in the individual of aberrant social relationships. Its particular characteristics depend on the nature and conditions that originate them". In the assay, it is expected that such consequences are only understood as the top of the iceberg and that we can extend to the possible responses of children and adolescents in the real conditions of the City. It is also intended that its identification will contribute to enhance the commitment of all sector involved, such as parents, educators, community leaders, public health workers, among others.